Becoming a teacher Research on the work-integrated learning of student teachers - Mentz, Elsa (NWU Self-Directed Learning Series, 2020)
This book disseminates original research on learning in and from practice in pre-service teacher education. Authors such as Lederman and Lederman describe the student teaching practicum (or work-integrated learning [WIL]), which is an essential component of pre-service teacher education, as the 'elephant in the room'. These authors note that 'the capstone experience in any teacher education programme is the student teaching practicum... [a]fter all, this is where the rubber hits the road'. However, many teacher educators will agree that this WIL component is sometimes very insufficient in assisting the student teacher to develop their own footing and voice as a teacher. This is the 'gap' that this research book addresses. Most of the chapters in the book report empirical data, with the exception of two chapters that can be categorized as systematic reviews. WIL is addressed from various angles in the chapters. Chapter 6 focuses on research related to what makes Finnish teacher education so effective, and in Chapter 4 researchers of the University of Johannesburg disseminate their findings on establishing a teaching school (based on Finnish insights) in Johannesburg. Chapter 3 highlights the challenges faced in open-and distance learning teacher education contexts. Several of the chapters disseminate research findings on alternative interventions to classic WIL, namely, where "safe spaces" or laboratories are created for student teachers to learn and grow professionally. These could either be simulations, such as software programmes and avatars in the intervention described in Chapter 2; student excursions, as the findings in chapters 5, 7 and 10 portray; or alternative approaches to WIL (e.g. Chapters 11 and 12). The book is devoted to scholarship in the field of pre-service teacher education. The target audience is scholars working in the fields of pre-service teacher education, work-integrated learning, and self-directed learning. The book makes a unique contribution in terms of firstly its extensive use of Cultural-Historical Activity Theory as a research lens, and secondly in drawing on various theoretical frameworks. Both quantitative and qualitative research informed the findings of the book.